2018
DOI: 10.5114/fn.2018.80870
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological correlation in case of BRAT1 mutation

Abstract: The clinical picture of BRCA1-associated protein required for ATM activation-1 (BRAT1) comprises retractable earlyonset epileptic encephalopathy, progressive microcephaly, and early demise. Both, inter-and intrafamilial variations of features of BRAT1-associated disease have been described. Here, the familial case of a brother and sister with homozygous pathogenic variants in BRAT1 is presented with special emphasis on differences in seizure type/onset and central nervous system lesions. The neuropathology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…Second, unlike most patients reported in the literature, he presented with migrating epilepsy. Finally, although progressive cerebral and cerebellar atrophy were demonstrated in the previously reported patients [4,[15][16][17][18][19], we observed pontocerebellar hypoplasia (PCH) in the present patient. We excluded additional variants in 28 PCH genes (Online Resource 2) including TSEN54 that could cause clinical findings similar to RMFSL [20].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Second, unlike most patients reported in the literature, he presented with migrating epilepsy. Finally, although progressive cerebral and cerebellar atrophy were demonstrated in the previously reported patients [4,[15][16][17][18][19], we observed pontocerebellar hypoplasia (PCH) in the present patient. We excluded additional variants in 28 PCH genes (Online Resource 2) including TSEN54 that could cause clinical findings similar to RMFSL [20].…”
Section: Discussioncontrasting
confidence: 66%
“…Micr − 4 SD + 2 month Facial myoclonus, focal dyscognitive, and secondarily generalized seizures Bilateral multifocal epileptiform activity Progressive cerebral and cerebellar atrophy, dysmyelination, and a region of focal encephalomalacia 15 months + Apnea, brachycephaly, thin lips, prominent ears, round nasal tip, bulbar dysfunction Celik [ 16 ] 1 M/+ Turkish Homozygous .2230_2237dupAACACTGC p.Ser747Thrfs*3 Prog. Micr − 3.7 SD + NK Myoclonic seizures of the limbs and face Background activity of – 6 Hz theta, bilateral frontotemporal sharp waves, and 8–10 Hz ictal rhythm during clinical seizures Progressive cerebral and cerebellar atrophy and thinning of the corpus callosum 10 months + Apnea, in utero abnormal movements, hyperreflexia Hegde [ 15 ] 1 F/+ Indian Homozygous c.617T>A p.Leu206* − 3.8 SD + 3 days Clonic seizures, eye blinks, and mouth movements, migrating partial epilepsy of infancy Occasional generalized bursts of epileptiform activity with relatively well-preserved background activity, burst suppression pattern Cortical and cerebellar atrophy with increased ventriculomegaly 4 months + Prominent forehead, bulbous nose, thin upper lip, retrognathia, camptodactyly Szymanska [ 18 ] 1 F/− NK Homozygous c.1313_1314delAG p.Gln438fs NA + 1 day Myoclonic NA ...…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the severity of disease is linked to zygosity of the BRAT1 variants with most of the reported homozygous cases developing seizures immediately after birth or suspected to have had seizures in utero . The longest reported survival for a homozygous patient is 12 months [16] . The reported cases with compound heterozygous BRAT1 variants, however, show a relatively delayed onset of seizures, typically within the first few months of life but in a few cases, after one year of age.…”
Section: Discussionmentioning
confidence: 99%
“… 4 months Skafi, 2018 [26] 1 Homozygous c.638_639dupA, p.(Val214Glyfs*189) Day 1 Myoclonic RMFSL Normal Low-voltage background without epileptic discharges. 3 months Szymańska, 2018 [16] 1 Homozygousc.1313_1314delAG, p. (Gln438Argfs*51) Day 1 Myoclonic RMFSL Cerebral atrophy, thinning of corpus callosum NA 6 months 2 Day 1 Myoclonic, tonic, clonic RMFSL Widened subarachnoid space Generalized and focal sharp and spike waves. 12 months Van Ommeren, 2018 [27] 1 Homozygous c.1395G > C, p.(Thr465Thr) Day 1 Myoclonic RMFSL Thinning of corpus callosum Diffuse encephalopathy, with frequent ictal activity from multiple cortical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Since the BRAT1 was first reported as the causative gene of RMFSL (Puffenberger et al, 2012), 45 mutations in the BRAT1 have been reported to date according to the Human Gene Mutation Database HGMD (http://www.hgmd.org/; Professional 2022.1) and the existing literature, including 20 missense/nonsense mutations, 8 splice mutations, 9 small deletions, 5 small insertions/duplications, and 3 gross deletions mutations (Figure 5, Table 1) (Capalbo et al, 2019; Colak et al, 2020; Fernández‐Jaén et al, 2016; Hanes et al, 2015; Heide et al, 2020; Li et al, 2021; Na et al, 2020; Qi et al, 2022; Scheffer et al, 2020; Szymańska et al, 2018; Wu et al, 2021). In this study, we found a sixth splice site mutation c.431‐2A>G (Colak et al, 2020; Horn et al, 2016; Srivastava et al, 2014; Stödberg et al, 2020; Rudolf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%